Metallo-functionalized first-generation salicylaldimine poly(propylenimine) tetraamine dendrimers: Electrochemical study and atomic force microscopy imaging - Martinovic, Jasmina (2008)
The adsorption and the redox processes of two first-generation salicylaldiamine dendritic ligands and their copper, cobalt and nickel metallo-functionalized complexes have been studied at two types of carbon electrode surface. Glassy carbon (GC) was used in an electrochemistry study and highly oriented pyrolitic graphite (HOPG) in ex situ atomic force microscopy (AFM) imaging. All salicylaldimine ligands and their metallo-functionalized complexes adsorb on the surface of the HOPG electrode, resulting in the formation of nanoclusters and films, which vary between 0.9 and 6 nm in size, depending on the metallo-functionalized salicylaldimine dendrimer chemical composition and solution concentration. Differential pulse voltammetry of the surface-confined films has shown that the anodic reactions observed correspond to the oxidation of the hydroxyl groups present in the ligand structure of all compounds. However, by following the changes in peak currents, potentials and width at half height it has been shown that destabilization of the ligand internal structure occurred in the metallo-functionalized complexes depending on the metal involved. The electrochemical behaviour of the surface-confined films observed in buffer solution was related to the morphology, obtained by AFM, of the immobilised first-generation salicylaldiamine dendritic ligands and corresponding salicylaldimine metallo-functionalized complexes.